AQUEOUS ALTERATION OF CHONDRULES IN THE CM CARBONACEOUS CHONDRITE, ALLAN HILLS 81002: IMPLICATIONS FOR PARENT BODY ALTERATION - Hanowski N.P.; Brearley A.J. (My University, 2001)
ALH 81002 is a CM carbonaceous chondrite that has petrographic characteristics suggesting that it experienced a high degree of aqueous alteration, but has entirely escaped parent body brecciation. In this study, we report the results of a systematic investigation of the alteration of more than 35 chondrules in ALH 81002 that belong to specific well-defined chondrule types. Our results show that the extent of chondrule alteration is almost exclusively controlled by the properties of the chondrule phases. Although these chondrules, taken as a group, show highly variable degrees of alteration, no evidence for differences in the alteration histories of chondrules has been found. Instead, the widely varying rates of alteration of chondrule phases, such as forsteritic and fayalitic olivine, clinoenstatite, orthopyroxene and augite are sufficient to explain the diversity of chondrule alteration in ALH 81002. Chondrules with similar primary textural and mineralogical characteristics (e.g., type IA, type IIA, etc.) show remarkably similar degrees of alteration. Detailed studies of the alteration products of chondrules show that they retain a detailed record of the alteration history of the chondrules from the earliest to last stages and provide strong evidence for the compositional evolution of the altering fluid. Contrary to what might be expected, the fluid composition appears to be the dominant controlling factor on the composition of serpentines that replace olivines, pyroxenes and mesostasis.The consistent degree of alteration observed in chondrules of the same type in ALH 81002 indicates that they were altered under the same conditions, for similar lengths of time. Such conditions are most consistent with alteration in a parent body environment. In addition, the compositional and textural uniformity of rim material, chondrule alteration phases and vein fillings in chondrule components throughout ALH 81002 also argue strongly that alteration occurred after accretion. Several observations on ALH 81002 provide additional constraints and modifications on existing models of in situ parent body alteration. For example, inferences on the degree of alteration of CM chondrites, based on the extent of brecciation as a parameter of the alteration degree, appear to be compromised. In addition, models which suggest that tochilinite/serpentine (PCP)-rich objects have resulted from the break up of chondrules during brecciation are also inconsistent with our observations on ALH 81002.